Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1086/680231
|View full text |Cite
|
Sign up to set email alerts
|

A Passionate Free Climber: Structural Development and Functional Morphology of the Adhesive Tendrils in Passiflora discophora

Abstract: Editor: Adrienne NicotraPremise of research. Passiflora discophora is exceptional among passion flowers for its climbing strategy, using branched tendrils with terminal adhesive pads instead of coiling tendrils as typical within this family. This article investigates the structural development and morphology of these adhesive pads and aims to understand the underlying structure-function relationship of the attachment process. Based on our results, we discuss possible mechanical consequences of the tendril stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…Nevertheless, some species from the subgenus Deidamioides show branched tendrils with terminal adhesive pads, a feature that is exclusive to this subgenus (Krosnick et al, 2013 ). This is the case in three species of Passiflora , i.e., Passiflora discophora, P. arbelaezii , and P. tryphostematoides (Bohn et al, 2015 ). Tendrils of P. discophora are 3-to-5 branched with terminal adhesive pads.…”
Section: A Special Case: Convergent Evolution Of Tendrils With Adhesimentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, some species from the subgenus Deidamioides show branched tendrils with terminal adhesive pads, a feature that is exclusive to this subgenus (Krosnick et al, 2013 ). This is the case in three species of Passiflora , i.e., Passiflora discophora, P. arbelaezii , and P. tryphostematoides (Bohn et al, 2015 ). Tendrils of P. discophora are 3-to-5 branched with terminal adhesive pads.…”
Section: A Special Case: Convergent Evolution Of Tendrils With Adhesimentioning
confidence: 99%
“…Tendrils of P. discophora are 3-to-5 branched with terminal adhesive pads. A recent developmental analysis of P. discophora revealed that tendrils perform contact coiling that is combined with the development of adhesive pads for climbing (Bohn et al, 2015 ). Before initial contact with a substrate, tendril apices are slightly hook shaped.…”
Section: A Special Case: Convergent Evolution Of Tendrils With Adhesimentioning
confidence: 99%
See 2 more Smart Citations
“…In this respect the hook structures of semi-self-supporting plants differ fundamentally from attachment devices of climbing plants which establish a much closer attachment to the host plants which is necessary as these climbers entirely have lost mechanical (self-)stability of their stems in older ontogenetic stages. Coiling tendrils, adventitious roots with root hairs or adhesive pads secure a much closer attachment to the host plants and adhere much firmer to their supporting structures [ 1 , 18 22 ]. In these plants typically flexible structures (e.g.…”
Section: Discussionmentioning
confidence: 99%